2017
DOI: 10.1063/1.4990981
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube wires with continuous current rating exceeding 20 Amperes

Abstract: A process to fabricate carbon nanotube (CNT) wires with diameters greater than 1 cm and continuous current carrying capability exceeding 20 A is demonstrated. Wires larger than 5 mm are formed using a multi-step radial densification process that begins with a densified CNT wire core followed by successive wrapping of additional CNT material to increase the wire size. This process allows for a wide range of wire diameters to be fabricated, with and without potassium tetrabromoaurate (KAuBr4) chemical doping, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…MWCNT fibers with large fiber diameters (100 µm to 6 mm) or poorer alignment show even lower ampacities of 10 6 A m −2 . [ 259,260 ] All together, these results suggest that improvements in density and alignment are more critical to ampacity than other factors such as doping.…”
Section: Extrinsic Characteristicsmentioning
confidence: 92%
“…MWCNT fibers with large fiber diameters (100 µm to 6 mm) or poorer alignment show even lower ampacities of 10 6 A m −2 . [ 259,260 ] All together, these results suggest that improvements in density and alignment are more critical to ampacity than other factors such as doping.…”
Section: Extrinsic Characteristicsmentioning
confidence: 92%
“…However, and even with these problems, there are some authors who claim to have developed high-ampacity power cables, made of closely packed and aligned carbon nanotubes [62], with values of ampacity close to 1 × 10 5 A/cm 2 . Other recent results have shown that by using a radial densification process, it is possible to obtain cables with a diameter up to 1 cm in size [63]. A densified core of CNTs is first produced, and then successive layers of CNTs are wrapped and densified on top.…”
Section: Cnt As High Ampacity Materialsmentioning
confidence: 99%
“…Mechanical testing took place by increasing the strain by 0.5%/min until yarn failure. The high-current characteristics of both the as-received yarn and yarns treated with IBr were measured using an Arbin BT-2000 power supply by applying a constant current through two source/measure probes (separated by 25 mm of yarn), which was increased every 30 s by 10 mA until wire failure, similar to procedures previously used to test high-current characteristics of CNT wires and yarns. , …”
Section: Methodsmentioning
confidence: 99%